Overt tumor regression after salvage boron neutron capture therapy (BNCT) for a recurrent glioblastoma patient - Lan, Tien-Li; Chou, Fong-In; Huang, Wen-Sheng; Lin, Ko-Han; Lee, Yi-Yen; Pan, Po-Shen; Kuo, Yu-Cheng; Hsu, Shih-Ming; Chang, Feng-Chi; Liang, Muh-Lii; Lee, Jia-Cheng; Lin, Shih-Chieh; et al. (Therapeutic Radiology and Oncology, 2018)
A 52-year-old woman was diagnosed with left parietal glioblastoma, and underwent craniotomy with near total tumor removal on October 11th, 2017. After the surgery, she received concurrent chemoradiotherapy (6,000 cGy in 30 fractions and daily oral temozolomide) and adjuvant monthly temozolomide for following 12 months. However, tumor relapse was noted during February 2018 by magnetic resonance imaging (MRI) examination. The tumor progressed rapidly, and patient experienced right limbs hemiplegia. Therefore, salvage BNCT was chosen as the treatment option. BNCT was performed at Tsing-Hua Open Pool Reactor on May 11th, 2018. During the entire treatment procedure, she continuously received L-BPA [L-(4-10borophenyl) alanine] 450 mg/kg of body weight via an intravenous infusion. Before the patient started epithermal neutron irradiation, her blood boron concentration was 27.72 ppm. The prescribed mean tumor dose to gross tumor volume was 20.44 Gy-E. Two weeks after BNCT, a MRI examination revealed overt tumor response with near complete tumor regression. BNCT is a useful salvage treatment for recurrent glioblastoma and is less toxic to the adjacent normal tissue.